Pengaruh hutang terhadap laba bersih (Studi pada PT. UNILEVER INDONESIA TBK.) - Suhartono, Suhartono; Damayanti, Widya; Kuspriyono, Taat; Hakim, Lukman; Abdurrachman, Abdurrachman; Agustina Yanti, Vera (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
PT Unilever Indonesia Tbk is a company engaged in manufacturing, marketing and product distribution. Debt is one source of capital in optimizing or developing company profits. The purpose of this study is to analyze the effect of debt on net income at PT Unilever Indonesia Tbk. This study uses quantitative methods, namely the data analysis method using statistical tests, namely the basic assumption test, correlation, coefficient of determination and linear regression equation. The sample data of this study were taken from the website of the BEI and PT Unilever Indonesia Tbk for the 2013-2020 quarter period, so that the data obtained were 32 data. Based on the results of the research, the correlation coefficient test of 0.311 shows that debt to net income has an insignificant, weak and unidirectional relationship. Partially there is no influence between debt on profit and loss (H0 is accepted, Ha is rejected). As for the linear regression equation, it is obtained Y=0.843 + 0.809X.